A vasculitic neuropathy case related to cryoglobulinaemic vasculitis - Akdaş, Akın; Yurtdaş, Mustafa; Bölek, Ertuğrul Çağrı; Panpallı Ateş, Mehlika (Acta Medica, 2025)
Vasculitis are a group of autoimmune disease which cause inflammation on vessel wall and vessel damage that leads to ischemia and necrotic damage in affected organs [1]. Vasculitic and autoimmune connective tissue disease can be a reason of peripheric neuropathy which will be hard to diagnose but also can be treatable [1]. Acute or sub-acute, painful, multifocal sensorial or sensorimotor polyneuropathy or asymmetric distal polyneuropathy may be the first sign of vasculitic disorder [1,2]. Acute motor sensorial axonal neuropathy (AMSAN) is a rare form of Guillain-Barre Syndrome which peripheral neurons has axonal damage and presenting with both motor and sensorial symptoms [3]. In this case report we will discuss the diagnostic period of a 76 years old patient who first evaluated as AMSAN in his polyclinic examination, tests and imaging’s than hospitalized for further investigation and detailed evaluation which ends up with diagnosed as Cryoglobulinemic Vasculitis.